Micropaleontology of the Reef Facies of the Pirabas Formation (Lower Miocene), Pará State, Brazil - Távora, Vladimir de Araújo; Souza, Bruna Leal Passos de; Nogueira Neto, Ignácio de Loiola Alvares (Anuário do Instituto de Geociências, 2017)
This work presents the resulting data from microfossils analysis of the Pirabas Formation reef lithofacies, exposed in the Maçarico beach, Salinópolis city, Pará State, Brazil. The specific diversity and abundance indicates reef environment developed in warm and shallow waters with high energy and high availability of calcium carbonate. The microfossils also suggest low to moderate sedimentation rate and variable substrate composition. The intense diagenesis appears to have dissolved many specimens but the strucuture of the primary orictocoenosis was preserved.